Growth and Development of Higher Education in Uttarakhand - Pavan Kumar; Joshi, P.K. (JOURNAL OF INDIAN EDUCATION, 2020)
Higher education institutions are the centers that provide opportunities to the youth to empower themselves through higher knowledge, attitude and skills, which are crucial for the progress of any nation or the society. Such empowerment is not only the basis of the development but is also responsible for ensuring better quality of life, progress and happiness. In the era of cutthroat competition, survival of any nation depends upon its higher education system, therefore, higher education is considered as key determinant of national growth. After independence, higher education sector in India has also witnessed manifold growth. Uttarakhand as new born state has also witnessed rapid changes in its higher education system in the recent past. Numbers of institutions including universities and colleges have also grown rapidly. The need therefore is to assess the status of higher education system in Uttarakhand as detailed in the present paper.